How to optimize the extraction of the spin angular momentum of an electromagnetic wave using resonances - Jodet, Côme; Pascal, Olivier; Sokoloff, Jérôme (European physical journal. Applied physics, 2025)
This paper is part of an ongoing study on the manipulation of objects using microwaves. The first step consists of rotating magnetic dipoles. The aim of this article is to approach this through a transfer of Angular Momentum (AM) from a microwave to an object and thereby studying the in influence of resonances in order to increase this transfer. Theoretical approaches supported by experimental work are provided. Previous results are revisited using an AM transfer approach. A simple analytical model is developed to study the role of a resonant cavity. This leads to the experimental spinning of a centimetric non-resonant copper ring in an electromagnetic resonant cavity, achieving several rotations within a few tens of seconds. The limitations and prospects of these results are discussed.